Identification and Pathogenicity Analysis of the Pathogen Causing Spotted Spleen in Muscovy Duck - Ke, Tianqiao; Yang, Dehong; Yan, Zhuanqiang; Yin, Lijuan; Shen, Hanqin; Luo, Cuifen; Xu, Jingyu; Zhou, Qingfeng; Wei, Xiaona; Chen, Feng (Frontiers in Veterinary Science, 2022)
Since September 2020, the clinical symptoms of Muscovy duck spleen spots have appeared in Guangdong, Guangxi, Jiangxi, Hunan, Hubei, and other provinces, resulting in a large number of Muscovy duck deaths and great economic losses. The absence of the typical clinical symptoms caused by pathogenic microorganisms makes the cause of the spotted spleen a mystery. High-throughput sequencing results suggested that Riemerella anatipestifer (R. anatipestifer) may be the pathogen. Then, R. anatipestifer was regarded as the research target for isolation, identification, and pathogenicity assessment. After biochemical test, PCR amplification, and serotype determination, it was confirmed that the isolated strain CZG-1 was serotype 15 R. anatipestifer. Typical spotted spleen symptoms were observed after CZG-1 infection. Furthermore, drug sensitivity assays showed the similar drug-resistant spectrum of R. anatipestifer serotype 15 to other serotypes; for example, all test strains were resistant to polymyxin, gentamicin, and neomycin. The CZG-1 strain has high pathogenicity, and its lethal dose of 50% (LD50) is 35.122 CFU/ml. Virulence gene determination showed that the CZG-1 strain had at least five virulence genes, bioF, TSS9-1, TSS9-2, PncA, and 0373Right. Above all, this study identified and proved that the pathogen of spotted spleen in ducks was R. anatipestifer serotype 15, which caused death of ducks without the typical symptoms of bacterial infection. The results of this study enriched the knowledge of symptom after R. anatipestifer infection, provided a reference to the identification of the pathogen of spotted spleen, and provided theoretical basis for prevention and control of spotted spleen.